Upfront blood microRNA test in LDCT-reluctant individuals: insights from the biomild trial - Gabriella Sozzi; Federica Sabia; Luigi Rolli; Miriam Segale; Paola Suatoni; Anna Zanghi; Margherita Ruggirello; Alfonso Marchianò; Mattia Boeri; Ugo Pastorino (Journal of Experimental & Clinical Cancer Research)
Abstract Background Low-dose computed tomography (LDCT) lung cancer screening can reduce mortality in high-risk individuals, but many individuals with a heavy smoking history may be reluctant to undergo radiologic examinations. A non-invasive blood test might help overcome this barrier. The BioMILD trial evaluated the combination of a plasma microRNA signature classifier (MSC) and LDCT for personalized lung cancer screening in 4,119 individuals who smoke or used to smoke. Based on BioMILD results, we aim to conduct a projection analysis to estimate the number of early lung cancers that could be detected if MSC were used as an initial screening tool for individuals reluctant to undergo LDCT. This model explores the potential of a biomarker-driven approach to address screening hesitation. Main body The analysis focuses on 3,139 volunteers meeting NLST criteria. At baseline, 24.9% tested MSC-positive. Over two years, 63 lung cancer cases were detected, with a significantly higher incidence among MSC-positive participants (4.1% vs. 1.1%, p < 0.001). A biomarker-driven approach, where only MSC-positive individuals undergo annual LDCT, was compared to standard LDCT screening for all participants. This strategy could identify 58.7% of lung cancers detected via standard screening, including 56.5% of early-stage cases. Raw cost analysis estimated a per-case lung cancer detection cost of ~€14,000 for the biomarker-driven strategy versus ~€12,000 for standard screening. Conclusion Upfront blood MSC test showed a reasonable sensitivity for lung cancer detection, including in early-stage disease, with affordable costs. Such a non-invasive blood test strategy might contribute to improve lung cancer screening endorsement in the high-risk population.